Analysis of the perceptions of fitness studio members toward pound fit and trampoline exercises in the weight loss - Kevin Waldo; Ilham Ilham (Institute of Information Technology and Social Science (IITSS), 2026)
This study examines the perceptions of fitness studio members in Jambi City toward Pound Fit exercise and trampoline exercise in the weight-loss process. The research used a descriptive qualitative method, with data collected through interviews with fitness studio members selected through purposive sampling. Data were analyzed using qualitative descriptive analysis, examining respondents' answers according to the research themes. The results indicate that fitness studio members in Jambi City generally hold positive perceptions of both Pound Fit and trampoline exercise in the weight-loss process. Members expressed varied yet complementary views regarding the two types of exercise. Perceptions of Pound Fit exercise tended to be favorable: most respondents considered it effective for promoting calorie burning and supporting weight loss, and its dynamic movements, adjustable intensity, and rhythmic musical accompaniment were seen as motivating factors that helped maintain exercise consistency. Pound Fit was also regarded as relatively easy to follow, allowing members to participate regularly and sustainably. Perceptions of trampoline exercise were likewise positive; it was viewed as enjoyable and similar to a recreational activity, which helped reduce boredom during workouts. Beyond contributing to calorie expenditure, trampoline exercise was perceived to improve balance, stamina, coordination, and core muscle strength, with its playful nature encouraging regular participation. Differences in preference were shaped by individual comfort, personal interest, and consistency: some members preferred Pound Fit, others favored trampoline exercise, and several believed that combining both produced more optimal results.